Extracranial bone metastases from recurrent anaplastic astrocytoma on FDG PET/CT: A case report a care-compliant article. Issue 23 (June 2017) - Li, Zu-Gui; Mu, Hai-Yu
Abstract: Objective: Extracranial bone metastases from astrocytoma are rare and frequently detected as part of multiorgan metastases. It is extremely rare for astrocytoma to have extracranial bone metastases alone. The importance of whole-body fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) imaging in evaluating extracranial metastasis (ECMs) has not been described effectively due to the rarity of this event. The purpose of our case report is to emphasize the role of FDG PET/CT in the assessment of tumor recurrence and extracranial bone metastases from anaplastic astrocytoma. Methods and materials: A 25-year-old woman was firstly admitted with a 4-month history of progressive blurred vision, and 2-month history of intermittent headache. Presurgical MRI imaging revealed a large mass in the left trigone of lateral ventricle. Subsequently, she underwent tumor resection, radiotherapy and chemotherapy. A final pathological diagnosis of anaplastic astrocytoma (WHO III) was made. Nearly 12 months after the surgery, the follow-up brain MR imaging revealed a contrast-enhanced lesion in the site of operative region. Whole-body FDG PET/CT imaging was performed to evaluate the situation. Results: Postoperative brain FDG PET/CT showed an abnormal focal FDG uptake corresponding to the contrast-enhanced lesion in the operative area, suggesting a tumor recurrence. Whole-body FDG PET/CT also showed multiple FDG-avid osteosclerotic lesions in the body. It was highly suggestive of extracranial bone metastases. A subsequent open bone biopsy of FDG-avid lesion in right iliac crest was performed. Histopathological and immunohistochemical findings indicated characteristic of glioma. The patient died 1 month later, nearly 13 months after the initial diagnosis. Conclusions: ECMs from anaplastic astrocytoma are extremely rare but they do occur. Whole-body FDG PET/CT imaging with inclusion of brain was valuable in differentiating tumor recurrence from radiation necrosis and in detecting uncommon extracranial bone metastases from anaplastic astrocytoma, which were closely related to prognosis of this disease.